Lightweight high-strength plastic Mg-Li-Zn-Gd alloy bar and preparation method thereof
By adding gadolinium and zinc elements to the magnesium lithium alloy and using extrusion molding and rotary forging processes to form a second phase with diffuse distribution, the problem of taking into account both tensile strength and plasticity of magnesium lithium alloy is solved, and a lightweight high-strength magnesium lithium alloy rod material with high strength and good plasticity is achieved.
Patent Information
- Application Number
- CN202411688546.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
After deformation processing, the tensile strength of magnesium lithium alloy is difficult to exceed 300MPa, and the plasticity is difficult to take into account, which hinders its further development in aerospace and other fields.
By adding gadolinium (Gd) and zinc (Zn) elements to the magnesium lithium alloy and using extrusion molding and rotary forging, the second phase of Mg3Zn3Gd2 and MgZn2 in diffusely distributed are formed, and the grains are refined and the strength and plasticity of the alloy are improved.
It has achieved high strength and good plasticity of magnesium lithium alloy, with a yield strength of 276MPa, a tensile strength of 303MPa, and an elongation of more than 24%, meeting the application needs in aerospace and other fields.
Smart Images

Figure CN119506626A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and in particular relates to a lightweight high-strength plastic Mg-Li-Zn-Gd alloy rod and a preparation method thereof. Background Art
[0002] As the lightest metal structural material at present, magnesium-lithium alloy has great application prospects in aerospace, national defense, electronic information and other fields due to its high specific strength and specific stiffness, excellent electromagnetic shielding performance, damping performance and low density. The addition of Li will change the lattice parameters and phase composition of the alloy, reduce the critical shear stress in the slip direction, make the slip system easier to start, and improve the plasticity, but the resulting low strength is a thorny problem that hinders the development of Mg-Li alloys. However, there is a mutually restrictive relationship between the plasticity, strength and density of magnesium-lithium alloys, which hinders its further development in aerospace and other fields. Therefore, the development of lightweight and high-strength magnesium-lithium alloys is of strategic significance. While improving the strength of magnesium-lithium alloys, the high plasticity and low density of the alloy should be guaranteed as much as possible, and the cost should be reduced.
[0003] In current research, alloying and deformation processing are two ways to strengthen magnesium-lithium alloys. Other elements are added to form solid solution strengthening and precipitation strengthening, and large plastic deformation is applied to further strengthen the alloy. However, after deformation processing, the tensile strength of magnesium-lithium alloys is difficult to exceed 300MPa. Even if high strength is achieved, it is difficult to have both plasticity and strength, which brings challenges to the preparation of magnesium-lithium alloys. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the main purpose of the present invention is to provide a light-weight, high-strength and plastic Mg-Li-Zn-Gd alloy bar and a preparation method thereof, which adopts a magnesium-lithium alloy with good coordinated deformation ability, extrudes it into a bar, and improves the strength of the alloy by rotary forging, and maintains good plasticity, so as to prepare a light-weight, high-strength magnesium-lithium alloy bar.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod comprises the following steps:
[0007] (1) preparing pure magnesium ingots, pure rolled ingots, pure zinc ingots, and pure lithium ingots;
[0008] (2) selecting the above raw materials according to the mass percentage of the selected alloy components in the lightweight and high-strength magnesium-lithium alloy rod, and heating and melting the selected raw materials in an argon atmosphere to prepare an alloy melt;
[0009] (3) casting the alloy melt obtained in step (2) to obtain an alloy ingot;
[0010] (4) preheating the alloy ingot obtained in step (3), and then extruding it to obtain an extruded rod of a magnesium-lithium alloy;
[0011] (5) The extruded rod obtained in step (4) is subjected to a rotary forging deformation treatment at room temperature to obtain a lightweight, high-strength, plastic magnesium-lithium alloy rod.
[0012] In some specific embodiments, the lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod includes, by weight percentage, 6-8% Li, 2-4% Zn, 2-4% Gd, and the rest is magnesium and unavoidable impurities.
[0013] In some specific embodiments, the heating and melting in step (2) is specifically as follows: the obtained raw materials are placed in a crucible and heated to 680-720° C. in a melting furnace until all the materials are completely melted to obtain an alloy melt.
[0014] In some specific embodiments, the casting molding in step (3) is specifically: after removing the waste slag at a temperature of 700-720°C, pouring into a stainless steel mold, cooling and molding in a vacuum chamber, and wire cutting to obtain an alloy ingot.
[0015] Furthermore, the cooling condition in the cooling molding is air cooling by a fan.
[0016] In some specific embodiments, the method further includes pre-treating the alloy ingot in step (3), specifically, removing the oxide scale or contamination layer on the surface of the alloy ingot obtained in step (3), and then cutting it into alloy ingots meeting relevant specifications.
[0017] Furthermore, the alloy ingot after turning can have a size of φ80 mm×300 mm.
[0018] In certain specific embodiments, the preheating conditions in step (4) are: preheating temperature is 230-250°C, and preheating time is 0.5-1.5h; the extrusion molding conditions are: extrusion ratio is (14-18):1, extrusion speed is 0.1-1mm / s, and extrusion temperature is 240-260°C.
[0019] In certain specific embodiments, the process conditions of the rotary forging deformation treatment in step (5) are as follows: the extruded rod obtained in step (4) is placed in a rotary forging machine for rotary forging at room temperature, and the rotary forging parameters are: a single-pass reduction of 3-5 mm, after 18-22 passes of rotary forging, a total reduction of 7-9 mm, and the rod diameter is reduced from 18-22 mm to 9-15 mm, thereby obtaining a lightweight, high-strength and plastic magnesium-lithium alloy rod.
[0020] A lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod prepared by the aforementioned preparation method.
[0021] Compared with the prior art, the present invention has at least the following advantages:
[0022] 1) The present invention adds gadolinium (Gd) with grain refining effect and zinc (Zn) with solid solution strengthening effect as main alloying elements to the magnesium-lithium alloy system, and simultaneously forms dispersed Mg3Zn3Gd2 and MgZn2 second phases during the extrusion-rotation forging process, especially MgZ n2 second phases distributed at the grain boundaries. According to the Zener pinning effect:
[0023]
[0024] Among them, r is the average radius of the pinned particles, φ is the volume fraction of the pinned particles, and d is the grain diameter. The statistics show that r = 9.6nm, φ = 0.0047, and the theoretical grain size diameter d is about 5.45μm, while the actual grain size is smaller than the theoretical grain size, which indicates that the second phase dispersed near the grain boundary pins the grain boundary and refines the grain more significantly.
[0025] 2) The segregation of solute atoms around grain boundaries and second phase particles. This segregation can change the energy state of the grain boundary. When the grain boundary moves, the distribution state of the solute atoms will change, so that additional energy is required to drive the grain boundary movement, which plays a role in pinning the grain boundary. The segregation of Zn elements around second phases such as Mg3Zn3Gd2 and MgZn2 can form a local high-concentration Zn area. This segregation may lead to local solid solution strengthening.
[0026] 3) Nano-second phase + Zn element segregation synergistically regulates and promotes each other. Zn element segregates near Mg3Zn3Gd2 and MgZn2 phases. On the one hand, this is related to the matching of the crystal structure. The crystal structures of Mg3Zn3Gd2 and MgZ n2 phases are both fcc. It is speculated that Zn atoms may have a good match with the fcc crystal structure in a specific direction; on the other hand, the segregation of Zn element near Mg3Zn3Gd2 and MgZn2 phases can lower the free energy of the entire alloy system and form more stable chemical bonds in the second phase. For the second phase itself, on the one hand, the segregation of Zn may help to enhance the stability and hardness of the second phase. Mg3Zn3Gd2 and MgZn2 phases may be more difficult to deform when Zn elements are segregated, thereby playing a better bearing role when the material is subjected to stress. On the other hand, the segregation of Zn can affect the nucleation and growth rate of the second phase. To a certain extent, a higher concentration of Zn may promote the nucleation of the second phase, thereby increasing the number of the second phase, and may also restrict its growth, making the second phase particle size smaller.
[0027] 4) The lightweight and high-strength magnesium-lithium alloy rods prepared by the present invention have a reduction of 4mm per pass, and the extruded rods are subjected to 10, 15, and 20 passes of rotary forging respectively; the tensile test results show that with the increase of the number of rotary forging passes, the strength of the alloy continues to increase, and the elongation decreases slightly. While the strength is continuously improved, the elongation is always maintained at more than 20%, combining strength and plasticity. Among them, the alloy with 20 passes of rotary forging has the best mechanical properties, with a yield strength of 276MPa, a tensile strength of 303MPa, an elongation of 24%, and a density of 1.564g / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0029] Figure 1 This is a stress-strain curve diagram of the magnesium-lithium alloy produced by hot extrusion-rotary forging process in Example 1 of the present invention;
[0030] Figure 2 This is a stress-strain curve diagram of the magnesium-lithium alloy produced by hot extrusion-rotary forging process in Example 2 of the present invention;
[0031] Figure 3 SEM images of cast magnesium-lithium alloys of Example 1, Example 2 and Example 3 of the present invention
[0032] Figure 4 The metallographic structure diagram of the magnesium-lithium alloy produced by hot extrusion process in Example 1, Example 2 and Example 3 of the present invention;
[0033] Figure 5 This is a metallographic structure diagram of a magnesium-lithium alloy produced by hot extrusion-rotary forging process in Example 3 of the present invention;
[0034] Figure 6 This is a SEM image of the magnesium-lithium alloy produced by hot extrusion process in Example 3 of the present invention;
[0035] Figure 7 This is a SEM image of the magnesium-lithium alloy produced by hot extrusion-rotary forging process in Example 3 of the present invention;
[0036] Figure 8 TEM image of magnesium-lithium alloy produced by hot extrusion-rotary forging process in Example 3 of the present invention (nano-MgZn2 particles pinning grain boundaries)
[0037] Fig. 9 TEM image of the magnesium-lithium alloy prepared by hot extrusion-rotary forging process in Example 3 of the present invention (Zn element is segregated near Mg3Zn3Gd2 and MgZn2 phases);
[0038] Fig.10 The stress-strain curve of the magnesium-lithium alloy prepared by hot extrusion-rotary forging process in Example 3 of the present invention is shown in FIG.
[0039] Fig.11 This is a stress-strain curve diagram of the magnesium-lithium alloy from the cast state to the extruded state and then to the rotary forging state according to Example 3 of the present invention. DETAILED DESCRIPTION
[0040] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0041] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0042] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0043] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0044] In the following embodiments, the pure magnesium ingots, pure rolled ingots, pure zinc ingots, and pure lithium ingots used are commercially available products, wherein the purity of the pure magnesium ingots is ≥99.95%, the purity of the pure rolled ingots is ≥99.97%, the purity of the pure zinc ingots is ≥99.99%, and the purity of the pure lithium ingots is ≥99.99%;
[0045] In the performance tests used in the following embodiments, the model of the tensile machine used is UTM4104; the model of the metallographic microscope used is OLYMPUS PMG3; and the model of the scanning electron microscope used is FEI NOVA 400.
[0046] Example 1
[0047] This embodiment provides a lightweight, high-strength, plastic magnesium-lithium alloy rod having the following components by mass fraction: Li: 7%, Zn: 3%, Gd: 3%, and the rest being magnesium and unavoidable impurities, wherein the total impurity content is ≤0.3%.
[0048] This embodiment provides a method for preparing a lightweight, high-strength, plastic magnesium-lithium alloy rod, comprising the following steps:
[0049] (1) selecting pure magnesium ingots, pure lithium ingots, pure gadolinium ingots, and pure zinc ingots as raw materials according to the mass percentage of the selected alloy components in the lightweight and high-strength magnesium-lithium alloy plate;
[0050] (2) Under the protection of argon gas, the raw materials obtained in step (1) are placed in a crucible in a vacuum furnace and heated to 720° C. along with the melting furnace until all the materials are completely melted to obtain an alloy melt;
[0051] In the alloy melting stage, the vacuum furnace is first evacuated to 2.5×10 -1 Pa, and then fill with argon as a protective gas until the vacuum furnace is completely melted under the atmosphere of the protective gas;
[0052] (3) stirring the alloy melt obtained in step (2) at a temperature of 710° C. until all raw materials are uniformly mixed, removing scum on the surface of the alloy melt, standing for 5 minutes, and then pouring it into a stainless steel mold with a diameter of Φ90 and a length of 300 mm. After naturally cooling in a vacuum chamber, the alloy ingot with a diameter of Φ80 is obtained by wire cutting;
[0053] (4) after removing the oxide scale or contamination layer on the surface of the alloy ingot obtained in step (3), the alloy ingot is placed in a heating furnace for preheating at a temperature of 250° C. and maintained for 1 hour, and then the preheated alloy ingot is extruded on an extruder at an extrusion temperature of 250° C., an extrusion ratio of 16:1, and an extrusion speed of 0-1 mm / s. After extrusion, the alloy ingot is cooled to room temperature by a fan to obtain an extruded rod with a diameter of 20 mm;
[0054] (5) The extruded rod obtained in step (4) is subjected to rotary forging deformation treatment at room temperature, with a single-pass reduction of 4 mm and 10 rotary forging passes, to finally obtain a magnesium-lithium alloy rod with a diameter of 16 mm.
[0055] The properties of the magnesium-lithium alloy rod prepared by the rotary forging deformation process at room temperature in step (5) of this embodiment were tested, and the results are as follows: Figure 1 As shown: yield strength is 218MPa, tensile strength is 255MPa, elongation is 28.7%, density is 1.565g / cm 3 .
[0056] The stress-strain curve of the Mg-Li-Zn-Gd alloy prepared by rotary forging at room temperature in this embodiment is shown in FIG. Figure 1 shown.
[0057] Example 2
[0058] This embodiment provides a lightweight, high-strength, plastic magnesium-lithium alloy rod having the following components by mass fraction: Li: 7%, Zn: 3%, Gd: 3%, and the rest being magnesium and unavoidable impurities, wherein the total impurity content is ≤0.3%.
[0059] This embodiment provides a method for preparing a lightweight, high-strength, plastic magnesium-lithium alloy rod, comprising the following steps:
[0060] (1) selecting pure magnesium ingots, pure lithium ingots, pure gadolinium ingots, and pure zinc ingots as raw materials according to the mass percentage of the selected alloy components in the lightweight and high-strength magnesium-lithium alloy plate;
[0061] (2) Under the protection of argon gas, the raw materials obtained in step (1) are placed in a crucible in a vacuum furnace and heated to 720° C. along with the melting furnace until all the materials are completely melted to obtain an alloy melt;
[0062] In the alloy melting stage, the vacuum furnace is first evacuated to 2.5×10 -1 Pa, and then fill with argon as a protective gas until the vacuum furnace is completely melted under the atmosphere of the protective gas;
[0063] (3) stirring the alloy melt obtained in step (2) at a temperature of 710° C. until all raw materials are uniformly mixed, removing scum on the surface of the alloy melt, standing for 5 minutes, and then pouring it into a stainless steel mold with a diameter of Φ90 and a length of 300 mm. After naturally cooling in a vacuum chamber, the alloy ingot with a diameter of Φ80 is obtained by wire cutting;
[0064] (4) after removing the oxide scale or contamination layer on the surface of the alloy ingot obtained in step (3), the alloy ingot is placed in a heating furnace for preheating at a temperature of 250° C. and maintained for 1 hour, and then the preheated alloy ingot is extruded on an extruder at an extrusion temperature of 250° C., an extrusion ratio of 16:1, and an extrusion speed of 0-1 mm / s. After extrusion, the alloy ingot is cooled to room temperature by a fan to obtain an extruded rod with a diameter of 20 mm;
[0065] (5) The extruded rod obtained in step (4) is subjected to rotary forging deformation treatment at room temperature, with a single-pass reduction of 4 mm and 15 rotary forging passes, to finally obtain a magnesium-lithium alloy rod with a diameter of 14 mm.
[0066] The properties of the magnesium-lithium alloy material of the rod prepared by the rotary forging deformation process at room temperature in step (5) of this embodiment were tested. The results are as follows: Figure 2 As shown: yield strength is 218MPa, tensile strength is 268MPa, elongation is 24.7%, density is 1.565g / cm 3 .
[0067] The stress-strain curve of the Mg-Li-Zn-Gd alloy prepared by rotary forging at room temperature in this embodiment is shown in FIG. Figure 2 shown.
[0068] Example 3
[0069] This embodiment provides a lightweight, high-strength, plastic magnesium-lithium alloy rod having the following components by mass fraction: Li: 7%, Zn: 3%, Gd: 3%, and the rest being magnesium and unavoidable impurities, wherein the total impurity content is ≤0.3%.
[0070] This embodiment provides a method for preparing a lightweight, high-strength, plastic magnesium-lithium alloy rod, comprising the following steps:
[0071] (1) selecting pure magnesium ingots, pure lithium ingots, pure gadolinium ingots, and pure zinc ingots as raw materials according to the mass percentage of the selected alloy components in the lightweight and high-strength magnesium-lithium alloy plate;
[0072] (2) Under the protection of argon gas, the raw materials obtained in step (1) are placed in a crucible in a vacuum furnace and heated to 720° C. along with the melting furnace until all the materials are completely melted to obtain an alloy melt;
[0073] In the alloy melting stage, the vacuum furnace is first evacuated to 2.5×10 -1 Pa, and then fill with argon as a protective gas until the vacuum furnace is completely melted under the atmosphere of the protective gas;
[0074] (3) stirring the alloy melt obtained in step (2) at a temperature of 710° C. until all raw materials are uniformly mixed, removing scum on the surface of the alloy melt, standing for 5 minutes, and then pouring it into a stainless steel mold with a diameter of Φ90 and a length of 300 mm. After naturally cooling in a vacuum chamber, the alloy ingot with a diameter of Φ80 is obtained by wire cutting;
[0075] (4) after removing the oxide scale or contamination layer on the surface of the alloy ingot obtained in step (3), the alloy ingot is placed in a heating furnace for preheating at a temperature of 250° C. and maintained for 1 hour, and then the preheated alloy ingot is extruded on an extruder at an extrusion temperature of 250° C., an extrusion ratio of 16:1, and an extrusion speed of 0-1 mm / s. After extrusion, the alloy ingot is cooled to room temperature by a fan to obtain an extruded rod with a diameter of 20 mm;
[0076] (5) The extruded rod obtained in step (4) is subjected to rotary forging deformation treatment at room temperature, with a single-pass reduction of 4 mm and 20 rotary forging passes, to finally obtain a magnesium-lithium alloy rod with a diameter of 12 mm.
[0077] The properties of the magnesium-lithium alloy material of the rod prepared by the rotary forging deformation process at room temperature in step (5) of this embodiment were tested. The results are as follows: Fig.10As shown: yield strength is 276MPa, tensile strength is 303MPa, elongation is 24%, density is 1.565g / cm 3 .
[0078] In addition, the present application also tests the metallographic structure and mechanical properties of the alloy in the embodiment, wherein the SEM of the cast Mg-7Li-3Zn-3Gd alloy is as follows: Figure 3 The metallographic structure of the Mg-7Li-3Zn-3Gd alloy extruded at 250°C is shown in Figure 4 As shown in Figure 2, the microstructure of the lightweight, high-strength plastic magnesium-lithium alloy prepared by rotary forging at room temperature is as follows: Figure 5 As shown, the SEM image of the extruded state is Figure 6 As shown, the SEM image of the rotary forging state is as follows Figure 7 As shown, TEM and EDS images are as follows Figure 8 and Fig. 9 As shown in Figure 2, the stress-strain curve of the rotary forging state is as follows: Fig.10 As shown in the figure, the stress-strain curve from the cast state to the extruded state and then to the rotary forging state is as follows Fig.11 shown.
[0079] As can be seen from the figure, the cast alloy presents a typical dendritic solidification structure, which is mainly composed of α-Mg phase, β-Li phase and second phase. The distribution of the second phase mainly has three forms, strips connected by thin lines, mesh eutectic structure and irregular small particles. The coarse second phase corresponds to the lower mechanical properties. The yield strength and tensile strength of the cast alloy are 112MPa and 143MPa respectively, and the elongation is 17%. The microstructure of the alloy after hot extrusion deformation has changed significantly. The dual-phase matrix structure and the black second phase are elongated along the extrusion direction. The original coarse dendritic and discontinuous mesh eutectic structure are crushed and become many fibrous second phases along the extrusion direction and small particles distributed along the phase boundary. Many fine equiaxed grains appear in the β-Li phase. The refined second phase, substructure and equiaxed crystals have greatly improved the strength and plasticity of the extruded alloy compared with the cast state. Its yield strength and tensile strength reach 173MPa and 211MPa respectively, and the elongation reaches 35.8%. After rotary forging, the dual-phase matrix structure of the alloy is further elongated, and the α-Mg and β-Li originally parallel to the extrusion direction have a tendency to form a cloud of mist. The second phase is broken into finer nano-scale particles. The Zn element is concentrated around these nanoparticles, restricting their growth and reducing the size of the second phase particles. The nanoparticles distributed at the grain boundaries pin the grain boundaries, further refining the grain size. Under the coordinated regulation of nano-precipitated phases such as Mg3Zn3Gd2 and MgZn2 + Zn element segregation, the yield strength and tensile strength of the rotary forged alloy reached 276MPa and 303MPa, respectively, which are 103MPa and 92MPa higher than the yield strength and tensile strength of the extruded alloy, respectively, and the plasticity remains at 24%.
[0080] The lightweight and high-strength magnesium-lithium alloy rod prepared by the present invention can be seen from the above examples and their data that the magnesium-lithium alloy material prepared by the present invention has high comprehensive performance at room temperature; after adding the Li element to the magnesium alloy, the c / a ratio of the α-Mg matrix can be changed, which promotes the start-up of the non-basal slip system, and also increases the coordination ability of the material during deformation, so that the plasticity of the material is further improved. Reasonable swaging passes and swaging reduction ensure that the Mg-7Li-3Zn-3Gd alloy grains are further refined after multiple small plastic deformations. The dispersion precipitation of nano-second phase particles Mg3Zn3Gd2 and MgZn2 near the grain boundary and the segregation of Zn around the second phase play a key role in improving the alloy performance, thereby making the magnesium-lithium alloy rod in the present invention show good performance.
[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod, characterized in that: The steps include: (1) preparing pure magnesium ingots, pure rolled ingots, pure zinc ingots, and pure lithium ingots; (2) selecting the above raw materials according to the mass percentage of the selected alloy components in the lightweight and high-strength magnesium-lithium alloy rod, and heating and melting the selected raw materials in an argon atmosphere to prepare an alloy melt; (3) casting the alloy melt obtained in step (2) to obtain an alloy ingot; (4) preheating the alloy ingot obtained in step (3), and then extruding it to obtain an extruded rod of a magnesium-lithium alloy; (5) The extruded rod obtained in step (4) is subjected to a rotary forging deformation treatment at room temperature to obtain a lightweight, high-strength, plastic magnesium-lithium alloy rod.
2. The method for preparing the lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod according to claim 1, characterized in that: The light-weight, high-strength and plastic Mg-Li-Zn-Gd alloy rod comprises, by weight percentage, 6-8% Li, 2-4% Zn, 2-4% Gd, and the remainder being magnesium and unavoidable impurities.
3. The method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod according to claim 1, characterized in that: The heating and melting in step (2) is specifically as follows: the obtained raw materials are placed in a crucible and heated to 680-720° C. in a melting furnace until all the materials are completely melted to obtain an alloy melt.
4. The method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod according to claim 1, characterized in that: The casting molding in step (3) is specifically as follows: after removing the waste slag at a temperature of 700-720°C, pouring into a stainless steel mold, cooling and molding in a vacuum chamber, and obtaining an alloy ingot by wire cutting.
5. The method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod according to claim 4, characterized in that: The method also includes pre-treatment of the alloy ingot in step (3), specifically, removing the oxide scale or contamination layer on the surface of the alloy ingot obtained in step (3), and then cutting it into alloy ingots that meet relevant specifications.
6. The method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod according to claim 1, characterized in that: The preheating conditions in step (4) are: preheating temperature is 230-250°C, and preheating time is 0.5-1.5h; the extrusion molding conditions are: extrusion ratio is 14-18:1, extrusion speed is 0.1-1mm / s, and extrusion temperature is 240-260°C.
7. The method for preparing a lightweight, high-strength and plastic Mg-Li-Zn-Gd alloy rod according to claim 1, characterized in that: The process conditions of the rotary forging deformation treatment in step (5) are as follows: the extruded rod obtained in step (4) is placed in a rotary forging machine for rotary forging at room temperature, and the rotary forging parameters are: a single-pass reduction of 3-5 mm, after 18-22 passes of rotary forging, a total reduction of 7-9 mm, and the rod diameter is reduced from 18-22 mm to 9-15 mm, thereby obtaining a lightweight, high-strength and plastic magnesium-lithium alloy rod.
8. A lightweight, high-strength and high-plasticity Mg-Li-Zn-Gd alloy rod prepared according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing high strength magnesium-lithium alloy
CN104004949A
Rotary swaging preparation method of light high-strength magnesium alloy
CN114346147A
Rotary die forging preparation method of ultralight high-strength magnesium-lithium alloy
CN114535478A
Smelting purification method of Mg-Li-Zn-Gd alloy for three-dimensional printing
CN115874074A
Ultra-strong and ultra-light dual-phase magnesium-lithium alloy and composite deformation process thereof
CN118086740A